Green Practices in Indian Healthcare Sector (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
With the emergence of industrial revolution, the concept of green practices has grown to become more than just a philosophy but a vital mission across the world. As the world has started moving towards ginormous environmental awareness, the anti - environmental policies practiced in pre industrialization period and in the initial stages of Industrial Revolution are no longer a feasible option. It has become essential that environment and industrialization must work together to attain sustainable development. Therefore the companies are adopting policies that not only improve their bottom line but also help protect the environment. The objective of this paper is to present the importance of green practices in healthcare and propose a model for ‘dimensions of green hospitals’ as well as highlight the efforts taken by Indian healthcare sector to become green and sustainable.
Keywords: green hospitals; Indian healthcare industry; green practices in hospitals; green purchasing; green building